Targeting Mitochondria-Located circRNA SCAR Alleviates NASH via Reducing mROS Output - Zhao, Qiyi; Liu, Jiayu; Deng, Hong; Ma, Ruiying; Liao, Jian-You; Liang, Huixin; Hu, Jingxiong; Li, Jiaqian; Guo, Zhiyong; Cai, Junchao; Xu, Xiaoding; Gao, Zhiliang; et al. (Cell, 2020)
Mitochondria, which play central roles in immunometabolic diseases, have their own genome. However, the functions of mitochondria-located noncoding RNAs are largely unknown due to the absence of a specific delivery system. By circular RNA (circRNA) expression profile analysis of liver fibroblasts from patients with nonalcoholic steatohepatitis (NASH), we observe that mitochondrial circRNAs account for a considerable fraction of downregulated circRNAs in NASH fibroblasts. By constructing mitochondria-targeting nanoparticles, we observe that Steatohepatitis-associated circRNA ATP5B Regulator (SCAR), which is located in mitochondria, inhibits mitochondrial ROS (mROS) output and fibroblast activation. circRNA SCAR, mediated by PGC-1α, binds to ATP5B and shuts down mPTP by blocking CypD-mPTP interaction. Lipid overload inhibits PGC-1α by endoplasmic reticulum (ER) stress-induced CHOP. In vivo, targeting circRNA SCAR alleviates high fat diet-induced cirrhosis and insulin resistance. Clinically, circRNA SCAR is associated with steatosis-to-NASH progression. Collectively, we identify a mitochondrial circRNA that drives metaflammation and serves as a therapeutic target for NASH. [Display omitted] •Mitochondria-located circRNA SCAR inhibits mROS output and fibroblast activation•circRNA SCAR shuts down mPTP by binding to ATP5B•Lipid-induced ER stress impairs PGC-1α-mediated circRNA SCAR expression•Mitochondria-specific delivery of circRNA SCAR alleviates metaflammation in vivo A mitochondrial circRNA that is dysregulated in NAFLD patients’ liver fibroblasts directly binds and regulates the mitochondrial permeability transition pore to modulate mitochondrial metabolism and inflammation, providing a potential therapeutic angle.